Parathyroid hormone 1 receptor is essential to induce FGF23 production and maintain systemic mineral ion homeostasis. Issue 1 (1st October 2015) - Fan, Yi; Bi, Ruiye; Densmore, Michael J.; Sato, Tadatoshi; Kobayashi, Tatsuya; Yuan, Quan; Zhou, Xuedong; Erben, Reinhold G.; Lanske, Beate
ABSTRACT: Parathyroid‐hormone‐type 1 receptor (PTH1R) is extensively expressed in key regulatory organs for systemic mineral ion homeostasis, including kidney and bone. We investigated the bone‐specific functions of PTH1R in modulating mineral ion homeostasis by generating a novel mouse model in which PTH1R is ablated in the limb mesenchyme using Prx1Cre transgenic mice. Such ablation decreased FGF23 protein and serum levels by 50%, despite normal Fgf23 mRNA levels in long bones. Circulating calcium and PTH levels were unchanged, but inorganic phosphate and 1, 25 (OH)2 D3 levels were significantly decreased and accompanied by elevated urinary calcium and phosphate wasting. Key renal genes for balancing mineral ion homeostasis, calbindinD28k, Klotho, and Napi2a were suppressed by 30‐40%. Intermittent hPTH(1‐34) injections increased Fgf23 mRNA (7.3‐fold), Nurr1 mRNA (3.1‐fold), and serum intact‐FGF23 (1.6‐fold) in controls, but failed to induce Fgf23, Nurr1 mRNA, or intact FGF23 production in mutants. Moreover, a significant elevation in serum C‐terminal‐FGF23 levels (4‐fold) was detected in both genotypes. PTH markedly down‐regulated Galnt3 expression (2.7‐fold) in controls but not in mutants. These results demonstrate the pivotal role of PTH1R in long bones to regulate systemic mineral ion homeostasis and the direct induction of FGF23 by PTH1R signaling.—Fan, Y., Bi, R., Densmore, M. J., Sato, T., Kobayashi, T., Yuan, Q., Zhou, X., Erben, R. G., Lanske, B. Parathyroid hormone 1 receptor is essential to induce FGF23 production and maintain systemic mineral ion homeostasis. FASEB J. 30, 428‐440 (2016). www.fasebj.org